UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KEJENUHAN BELAJAR SISWA KELAS IV SD NEGERI 1 BUNGI - Irma; Abdul Rahim; Darmayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article examines the efforts of Islamic Religious Education teachers in overcoming learning boredom among fourth-grade students at SD Negeri 1 Bungi. Learning boredom is one of the common problems in the learning process, characterized by a decline in students’ interest, motivation, and participation, particularly in Islamic Religious Education subjects. This study aims to describe the forms of learning boredom experienced by students, analyze the factors contributing to learning boredom, and examine the strategies employed by Islamic Religious Education teachers to address this issue. The research adopts a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving Islamic Religious Education teachers and fourth-grade students. The collected data were analyzed using qualitative data analysis techniques, including data condensation, data display, and conclusion drawing. The findings indicate that learning boredom is influenced by internal factors, such as low learning motivation and concentration, as well as external factors, including the use of less varied teaching methods and limited learning media. The efforts undertaken by Islamic Religious Education teachers to overcome learning boredom include varying teaching methods, utilizing simple instructional media, implementing active and enjoyable learning activities, and providing motivation and role modeling. This study concludes that the role of Islamic Religious Education teachers is crucial in creating a conducive and engaging learning environment, thereby minimizing students’ learning boredom and enhancing the quality of Islamic Religious Education learning.